The Influence Of Organizational Commitment, Job Satisfaction, and Leadership Support on Employee Retention - Farawowan, Fauziah F.; Damanik, Lisa Gresti Sella; Tulak, Grace Tedy (Journal Management & Economics Review (JUMPER), 2025)
Employee retention has become a critical issue for organizations in today’s highly competitive business environment. High turnover rates not only increase recruitment and training costs but also disrupt organizational stability and long-term performance. This study examines the influence of organizational commitment, job satisfaction, and leadership support on employee retention. Using a quantitative research approach with survey data collected from employees across various sectors, statistical analyses were conducted to evaluate the relationships among these variables. The findings reveal that organizational commitment, job satisfaction, and leadership support each have significant positive effects on employee retention, both individually and collectively. Employees who are emotionally committed, satisfied with their work conditions, and supported by their leaders are more likely to remain within the organization. The results confirm the relevance of Social Exchange Theory, Herzberg’s Two-Factor Theory, and Leader-Member Exchange Theory in explaining employee retention behavior. Practically, the study underscores the importance of developing integrated human resource strategies that foster organizational commitment, enhance job satisfaction, and strengthen leadership support to reduce turnover. Limitations and recommendations for future research are also discussed, including the need for longitudinal studies and the exploration of additional variables such as organizational culture and work-life balance.